The Impact of Net Profit Margin, Return on Assets, and Return on Equity on the Stock Prices of Telecommunications Companies in Indonesia - Mustafa Mustafa; Hajar Hajar; Adnan Hasan (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study aims to analyze the effect of profitability ratios—comprising net profit margin, return on assets, and return on equity—on the stock prices of telecommunications companies listed on the Indonesia Stock Exchange during the observation period. Research Design and Methodology: This study employs a quantitative approach using secondary data sourced from financial statements and stock prices of telecommunications companies for the period from 2015 to 2020. The research sample was determined using purposive sampling, resulting in five companies that met the data completeness criteria. Data analysis was conducted using multiple linear regression supported by classical assumption tests, hypothesis testing, and the coefficient of determination using SPSS software. This study employs a quantitative approach using secondary data sourced from financial statements and stock prices of telecommunications companies from 2015 to 2020. The research sample was determined using purposive sampling, resulting in five companies that met the data completeness criteria. Data analysis was performed using multiple linear regression supported by classical assumption tests, hypothesis testing, and the coefficient of determination using SPSS software. Findings and Discussion: The results of the study show that net profit margin and return on equity have a significant relationship with stock prices, while return on assets shows a weaker relationship. These findings indicate that profitability indicators based on earnings and returns to shareholders are more relevant in determining the market value of telecommunications companies than the efficiency of asset utilization. Implications: This study provides an empirical basis for investors and company management to use specific profitability ratios as key indicators in assessing and managing stock value in the telecommunications sector.